Disseminated toxoplasmosis after allogeneic stem cell transplantation in a seronegative recipient. Issue 1 (20th December 2012) - Osthoff, M.; Chew, E.; Bajel, A.; Kelsey, G.; Panek‐Hudson, Y.; Mason, K.; Szer, J.; Ritchie, D.; Slavin, M.
Abstract Toxoplasmosis is increasingly diagnosed after hematopoietic stem cell transplantation (HSCT) and is associated with considerable morbidity and mortality. In the majority of cases, reactivation of latent disease secondary to impaired cellular and humoral immunity after HSCT is believed to be the main pathogenetic mechanism. Hence, primary toxoplasmosis is rarely considered in the differential diagnosis of infections after HSCT in a recipient who is seronegative for Toxoplasma gondii pre‐transplant. We herein report a seronegative patient with acute T‐cell lymphoblastic leukemia, who developed primary disseminated toxoplasmosis 5 months after HSCT from a seronegative unrelated donor. A review of all reported cases of primary toxoplasmosis after HSCT revealed significantly increased morbidity and mortality. Patients with negative pre‐transplant Toxoplasma serology should therefore be considered at risk for toxoplasmosis after allogeneic HSCT. Possible prevention and monitoring strategies for seronegative recipients are reviewed and discussed in detail.